The Use of Virtual Reality to Improve Nutritional Fulfillment in Hospitalized Children: A Systematic Review - Yelly Sari Arifin; Dessie Wanda; Ayu Widya Lestari; Etty Rekawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Hospitalized children often experience decreased appetite, which is influenced by stress and anxiety. This decrease in appetite can worsen the recovery process and increase the risk of complications. VR technology has emerged as one of the promising innovations to reduce anxiety and improve nutritional fulfillment in children during medical treatment. Objective: To evaluate the effectiveness of Virtual Reality (VR) in improving nutritional fulfillment in hospitalized children. Method: A literature search was conducted on four major databases: PubMed, ProQuest, ScienceDirect, and Scopus. Three articles with Randomized Controlled Trial (RCT) design that met the inclusion criteria were selected and analyzed in this review. The articles were evaluated using the Joanna Briggs Institute (JBI) form to assess risk of bias and methodological quality. Results: This study shows that VR is more effective than animated videos in reducing anxiety, increasing appetite, and motivating children to eat nutritious food. In addition, VR also provides benefits as an interactive educational tool that appeals to children. Conclusion: VR is a promising intervention in improving nutritional fulfillment in hospitalized children. This technology not only reduces anxiety, but also has the potential to increase children's participation in the recovery process. Further research with larger samples is needed to confirm these findings and explore the applicability of VR to different age groups and diverse medical conditions.